A History of Radionuclide Studies in the UK 50th Anniversary of the British Nuclear Medicine Society - McCready, Ralph; Gnanasegaran, Gopinath; Bomanji, Jamshed B. (Springer Nature, 2016)
nuclear medicine; history of medicine